Recobrimento biomimético em superfícies de titânio e aço inoxidável austenítico - Coelho, Mariny Fabiéle Cabral (2013)
Titanium and stainless steel are examples of biomaterials widely used in dental and orthopedic implants, due to their characteristics for this application, such as corrosion resistance and excellent biocompatibility. Researches have been performed to obtain a coating in order to improve the adhesion between the bone and implant by modifying the metal surface, allowing for effective regeneration of bone tissue, osseointegration, and accelerating its growth. In this work, studied the effect of coating of biomimetic method on titanium (cp-Ti) and AISI 316L stainless steel, which consists in immersing the substrate in a solution of synthetic SBF (Simulated Body Fluid), composition, pH and temperature similar to blood plasma. The coating on both metals, was effective for obtaining hydroxyapatite, which was confirmed through the techniques of SEM, XRD and infrared. The bioactivity test showed excellent bioactive characteristics through of formation and development of hydroxyapatite on the receiving coating substrates with 1.5 SBF. For the substrates, cp-Ti and 316L austenitic stainless steel that have not received prior treatment or coating, the bioactivity test revealed only the bioactivity of cp-Ti. The polarization curves showed that the uncoated cp-Ti and 316L austenitic stainless steel with coating had better corrosion resistance at temperatures of 25ºC and 36.5°C. The uncoated cp-Ti showed as the most indicated biomaterial for implants, since it showed better bioactive characteristics and corrosion resistance.